2020
DOI: 10.7554/elife.52946
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drug modifiers for RYR1-related myopathy using a multi-species discovery pipeline

Abstract: Ryanodine receptor type I-related myopathies (RYR1-RMs) are a common group of childhood muscle diseases associated with severe disabilities and early mortality for which there are no available treatments. The goal of this study is to identify new therapeutic targets for RYR1-RMs. To accomplish this, we developed a discovery pipeline using nematode, zebrafish, and mammalian cell models. We first performed large-scale drug screens in C. elegans which uncovered 74 hits. Targeted testing in zebrafish yielded posit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Sarcopenia research would F I G U R E 1 Summary of genetic manipulations and therapeutic strategies that have been found to alleviate sarcopenia in rodents, Drosophila, and/or Caenorhabditis elegans greatly benefit from the use of Drosophila and C. elegans to identify more therapeutic strategies and the use of rodents to then test those therapies further. Such an "evolutionary pipeline" approach was reported recently to identify small molecules that might be useful for treating RYR1-related myopathies (Benian & Choo, 2020;Volpatti et al, 2020). Currently, research in rodents has been focused on muscle regeneration instead of muscle maintenance despite the known depletion of muscle satellite cells during aging (Garcia-Prat, Sousa-Victor, & Munoz-Canoves, 2013;Jones & Rando, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia research would F I G U R E 1 Summary of genetic manipulations and therapeutic strategies that have been found to alleviate sarcopenia in rodents, Drosophila, and/or Caenorhabditis elegans greatly benefit from the use of Drosophila and C. elegans to identify more therapeutic strategies and the use of rodents to then test those therapies further. Such an "evolutionary pipeline" approach was reported recently to identify small molecules that might be useful for treating RYR1-related myopathies (Benian & Choo, 2020;Volpatti et al, 2020). Currently, research in rodents has been focused on muscle regeneration instead of muscle maintenance despite the known depletion of muscle satellite cells during aging (Garcia-Prat, Sousa-Victor, & Munoz-Canoves, 2013;Jones & Rando, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish were presented as an aging model in 2002 by Gerhard et al who investigated the process of zebrafish aging and later demonstrated that it is comparable to human aging and suitable to study age-dependent changes in musculoskeletal function (Gerhard, 2003;. Zebrafish as a model for aging has also been supported by the work of Kishi et al (Kishi, 2004;Kishi et al, 2003) The ease of care, prolific breeding, easy genetic manipulability, and ability to readily absorb drugs through their water make the zebrafish an attractive model to work with (Daya, Donaka, & Karasik, 2020;Maves, 2014;Volpatti et al, 2020).…”
Section: The Modelmentioning
confidence: 99%
“…Zebrafish are smaller, have lower maintenance costs and produce much larger broods for generating large numbers of animals for analyses; there is also the simplicity of administering candidate drugs in their water. Although the method described here uses adults and is not suitable for the high-throughput drug screens used on zebrafish larvae ( Gallardo et al, 2015 ), it may provide a valuable addition to current drug screening protocols targeted at genetic diseases that have no larval phenotype but present a later movement disorder, as part of a multifaceted approach ( Volpatti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some limitations (Gut et al, 2017), these genome-editing approaches allow for the generation of a theoretically unlimited number of zebrafish mutants, which could ultimately enable scientists to systematically and comprehensively study full allele series for disorders such as LAMA2-MD. Lastly, performing genetic modifiers screens in caf zebrafish with methodologies including ENU mutagenesis and CRISPR gene editing (McGovern et al, 2015;Quattrocelli et al, 2017a,b;Rahit and Tarailo-Graovac, 2020;Volpatti et al, 2020) should enable the identification of genetic interactions and novel disease modifiers, data which would greatly advance our understanding of the pathomechanisms and phenotypic variability of LAMA2-MD.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true concerning therapy development, where a pipeline of large scale drug screening in zebrafish combined with testing and validation in the mouse may yield candidate therapeutics with the highest potential for successful translation to patients. The establishment of a similar pipeline crossing multiple species was recently reported for congenital muscle disease due to RYR1 mutation (Volpatti et al, 2020).…”
Section: Caveats Of Using Zebrafish As the Lama2-md Disease Modelmentioning
confidence: 93%